Aurora B and Aurora C pools at two chromosomal regions collaboratively maintain chromosome alignment and prevent aneuploidy at the second meiotic division in mammalian oocytes - Kouznetsova, Anna; Valentiniene, Sonata; Liu, Jian-Guo; Kitajima, Tomoya S.; Brismar, Hjalmar; Höög, Christer (Frontiers in Cell and Developmental Biology, 2024)
Correct chromosome segregation is essential to preserve genetic integrity. The two protein kinases, Aurora B and its meiotic homolog Aurora C, regulate attachments between chromosomal kinetochores and microtubules, thereby contributing to the accuracy of the chromosome segregation process. Here we performed a detailed examination of the localization and activity of Aurora B/C kinases, their partner Incenp and the kinetochore target Hec1, during the second meiotic division in mouse oocytes. We found that a majority of Aurora B and C changed their localization from the outer kinetochore region of chromosomes at prometaphase II to an inner central region localized between sister centromeres at metaphase II. Depletion of the Aurora B/C pool at the inner central region using the haspin kinase inhibitor 5-iodotubercidin resulted in chromosome misalignments at the metaphase II stage. To further understand the role of the Aurora B/C pool at the central region, we examined the behaviour of single chromatids, that lack a central Aurora B/C pool but retain Aurora B/C at the outer kinetochores. We found that kinetochore-microtubule attachments at single chromatids were corrected at both prometaphase II and metaphase II stages, but that single chromatids compared to paired chromatids were more prone to misalignments following treatment of oocytes with the Aurora B/C inhibitory drugs AZD1152 and GSK1070916. We conclude that the Aurora B/C pool at the inner central region stabilizes chromosome alignment during metaphase II arrest, while Aurora B/C localized at the kinetochore assist in re-establishing chromosome positioning at the metaphase plate if alignment is lost. Collaboratively these two pools prevent missegregation and aneuploidy at the second meiotic division in mammalian oocytes.